2005
DOI: 10.1099/mic.0.28039-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nearly identical morpholine monooxygenase-encoding mor genes from different Mycobacterium strains and characterization of the specific NADH : ferredoxin oxidoreductase of this cytochrome P450 system

Abstract: Cloning and sequencing of the morABC operon region revealed the genes encoding the three components of a cytochrome P450 monooxygenase, which is required for the degradation of the N-heterocycle morpholine by Mycobacterium sp. strain HE5. The cytochrome P450 (P450 mor ) and the Fe 3 S 4 ferredoxin (Fd mor ), encoded by morA and morB, respectively, have been characterized previously, whereas no evidence has hitherto been obtained for a specifically morpholine-induced reductase, which would be required to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…This is in contrast to the case in KTR9, where xplB and xplA occur downstream of glnA. The nucleotide sequence repeats present in the mor/pip loci (29,39,50) are absent in the xpl cluster.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…This is in contrast to the case in KTR9, where xplB and xplA occur downstream of glnA. The nucleotide sequence repeats present in the mor/pip loci (29,39,50) are absent in the xpl cluster.…”
Section: Discussioncontrasting
confidence: 44%
“…PCR analysis of KTR9 DNA genomic template with primers that flank the gene fusion point confirmed that there is no gap between these genes (data not shown). Interestingly, the glutamine synthase portion of the glnA-xplB fusion and XplR share up to 70% and 49% sequence identity, respectively, with the glutamine synthases and GntR-type regulators encoded by genes associated with the mycobacterial cyp151 genes (29,39,50). The organization of the xpl gene cluster suggests that it may constitute an operon that is regulated by XplR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Poupin et al [8] presented evidence for involvement of Cytochrome P450 (CYP) in the initial oxidation of morpholine utilizing an environmental Mycobacterium strain. For the first time proteins involved in morpholine degradation were isolated and characterized by Sielaff et al [15,16] who purified Cytochrome P450 mor and its putative redox partner, a Fe 3 S 4 ferredoxin (Fd mor ).…”
Section: Introductionmentioning
confidence: 99%